Media Massa, Kepentingan Publik dan Kekerasan Atas Nama Agama - Nyarwi Ahmad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
One of the most dynamic tension in Indonesian contemporary public’s awareness is the relationship among mass media, public interest and violence act in the name of religion. Here, three crucial issues will be discussed : 1) how is the changing and challenging in the relationship among mass media, public interest and violence in the name of religion in Indonesian context; 2) how did the religious values dominated public lives and constructed their public interest ; and 3) how did the public interest and expectation of mass media’s rules in the public minds tend be constructed unperfectly. Based on qualitative method, I propose that the dynamic domination of religious values will construct the public interest and it tend to navigate the mass media performance as well as their consumer’s expectations, but it will raise the unfinished dilemma in defining and searching of the best formula of mass media performance and their public responsibilities.